Role of the DNA repair glycosylase OGG1 in the activation of murine splenocytes - Seifermann, Marco; Niehrs, Christof (DNA repair, 2017)
OGG1 (8-oxoguanine-DNA glycosylase) is the major DNA repair glycosylase removing the premutagenic DNA base modification 8-oxo-7,8-dihydroguanine (8-oxoG) from the genome of mammalian cells. In addition, there is accumulating evidence that OGG1 and its substrate 8-oxoG might function in the regulation of certain genes, which could account for an attenuated immune response observed in Ogg1−/− mice in several settings. Indications for at least two different mechanisms have been obtained. Thus, OGG1 could either act as an ancillary transcription factor cooperating with the lysine-specific demethylase LSD1 or as an activator of small GTPases. Here, we analysed the activation by lipopolysaccaride (LPS) of primary splenocytes obtained from two different Ogg1−/− mouse strains. We found that the induction of TNF-α expression was reduced in splenocytes (in particular macrophages) of both Ogg1−/− strains. Notably, an inhibitor of LSD1, OG-L002, reduced the induction of TNF-α mRNA in splenocytes from wild-type mice to the level observed in splenocytes from Ogg1−/− mice and had no influence in the latter cells. In contrast, inhibitors of the MAP kinases p38 and JNK as well as the antioxidant N-acetylcysteine attenuated the LPS-stimulated TNF-α expression both in the absence and presence of OGG1. The free base 8-oxo-7,8-dihydroguanine had no influence on the TNF-α expression in the splenocytes. The data demonstrate that OGG1 plays a role in an LSD1-dependent pathway of LPS-induced macrophage activation in mice.